In‐vivo assessment of T cell kinetics in individuals at risk for type 1 diabetes. (7th October 2019) - Hao, W.; Bahnson, H. T.; Speake, C.; Cerosaletti, K.; Greenbaum, C. J.
Summary: We previously assessed the kinetics of T cell turnover in vivo by labeling cells with 2 H‐H2 O over 42 days in individuals with type 1 diabetes (T1D) and demonstrated an increased turnover of CD4 memory T cells. We have now tested T cell turnover in individuals at risk for T1D using a 3–4‐day labeling protocol with 2 H‐glucose. We studied 30 relatives with T1D with and without autoantibodies, and 10 healthy controls. Peripheral blood mononuclear cells (PBMC) were flow‐sorted into T cell subsets of interest; 2 H‐DNA enrichment was measured by mass spectrometry and in‐vivo turnover was calculated as maximum fractional enrichment of deuterated adenosine ( F max ). Among CD4 + cells, F max was highest in regulatory T cells (Treg ), followed by effector and central memory T cells and lowest in naive cells. Similarly, CD8 + central and effector memory T cells had a higher turnover than CD8 + terminally differentiated effector memory T cells (TEMRA) and CD8 + ‐naive T cells. Relatives as a group showed significantly increased Treg turnover by F max compared to controls (1·733 ± 0·6784% versus 1·062 ± 0·3787%, P = 0·004), suggesting pre‐existing immune dysfunction within families with T1D. However, there was no significant difference in F max between groups according to autoantibody or glucose tolerance status. Repeat testing in 20 subjects 1 year later demonstrated relatively higher within‐subject compared to between‐subject variability for the measurement of F max in various T cell subsets. The short labeling protocol with 2 H‐glucose should be applied in the context of a clinical trial in which the therapy is expected to have large effects on T cell turnover. Abstract : We tested T cell turnover in individuals at risk for T1D using a 3–4‐day labeling protocol with 2 H‐glucose. We found that relatives as a group showed significantly increased Treg turnover by F max compared to controls, suggesting pre‐existing immune dysfunction within families with T1D.